Upaya Orang Tua dalam Meningkatkan Pendidikan Agama Islam Terhadap Anak di SDN 08 Sentosa Kecamatan Dua Koto Kabupaten Pasaman - Ishardi (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2021)
This study aims to describe the efforts of parents in improving Islamic religious education for children in SDN 08 Sentosa Kecamatan Dua Koto Kabupaten Pasaman. This research uses qualitative research using observation, interview and documentation methods. While data analysis is by reducing data, presenting data, and making conclusions. The results showed that first: Parental guidance towards children can improve children's Islamic religious education, because parents are the foundations of education for children in the family which will then become the basis for the child's personality in the future. Second: the discipline of children to study at home can be realized with parental supervision. Third, to support the achievement of children's Islamic religious education, the role of parents can encourage children at home including attention to the learning process, giving advice, giving gifts and educational punishments, and providing sustainable children's learning facilities.